Dental discriminant sexing of human cremated remains - Kaczmarek, Maria; Piontek, Janusz; Malinowski, Andrzej (Anthropological Review, 1986)
In this paper set of discriminant functions, based on mesiodistal and buccolingual diameters of teeth crowns is presented. It is possible to use them in assessing sex of immature individuals from cremated graves.